2019
DOI: 10.1111/hex.12955
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a sense of security in everyday life—A case study of patients and professionals moving towards co‐production in an atrial fibrillation “learning café”

Abstract: BackgroundAn improvement initiative sought to improve care for atrial fibrillation (AF) patients; many felt insecure about how to cope with AF.ObjectiveTo reveal AF patients' and professionals' experiences of pilot‐testing a Learning Café group education programme, aimed at increasing the patients' sense of security in everyday life.DesignUsing an organizational case study design, we combined quantitative data (patients' sense of security) and qualitative data (project documentation; focus group interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In this regard, Fledderus et al 17 pointed to financial or nonmaterial rewards as the joy or intrinsic motivation of coproducing, which can be reflected in social recognition or group identity, as was the case for many of the young people in the studies we reviewed. Furthermore, the results of this study coincide with the findings from the literature on coproduction for the adult population 36–38 …”
Section: Discussionsupporting
confidence: 89%
“…In this regard, Fledderus et al 17 pointed to financial or nonmaterial rewards as the joy or intrinsic motivation of coproducing, which can be reflected in social recognition or group identity, as was the case for many of the young people in the studies we reviewed. Furthermore, the results of this study coincide with the findings from the literature on coproduction for the adult population 36–38 …”
Section: Discussionsupporting
confidence: 89%
“…Our study raises many questions about population‐level variation in care utilization in Sweden. Healthcare systems in Sweden and elsewhere often aim to move a person with a chronic disease from the group needing specialist care to primary care and to involve peer support from networks and, when, if possible, to self‐care (Suutari et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has already been proposed by Kokorelias et al who have identified core aspects of family focused care such as illness specific education. Furthermore, the need to focus on both the patient and the family members was mirrored in a study of patients’ and professionals’ experiences of pilot-testing a Learning Café group education program for patients with AF and family members [ 30 ]. The study demonstrated that patients´ overall sense of security increased after the session.…”
Section: Discussionmentioning
confidence: 99%